Development of a mathematical model of the system of integrated radio ecological monitoring of dniprodzerzhynsk town - Ковач, Валерія Омелянівна (Eastern-European Journal of Enterprise Technologies, 2014)
Seven tailings dams and two uranium waste storages were formed in the Dniprodzerzhynsk city (Ukraine) in the PA "Pridneprovsky Chemical Plant" (PA "PCP") influence zone after a long mining and processing of uranium ore (1949 - 1991). Protective covers of most tailings dams and engineering facilities of the uranium production infrastructure in the PA "PCP" territory are poor and getting worse every year under the influence of natural factors and because of the lack of remedial operations. Given the current difficult economic situation in Ukraine, least-cost creation of an effective system of integrated automated radioecological monitoring of the Dniprodzerzhynsk industrial - urban agglomeration area and influence zone of tailings dams is necessary. This was proposed to do by using a mathematical description of the monitoring system through the control loop, which describes the elements of influence on the management object in accordance with the received commands. The measurement results in the management object state are fixed by observation elements and a new management cycle begins. This differs from the systems, previously suggested for this area since the proposed control loop can be used not only for fixed, but also for mobile posts. The developed mathematical model has allowed to justify the optimal number of posts that are be placed in the Dniprodzerzhynsk industrial - urban agglomeration and the influence zone of tailings dams to control the difficult ecological situation in the given area.